2008
DOI: 10.1007/s11999-007-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone Grafting Severe Glenoid Defects in Revision Shoulder Arthroplasty

Abstract: During revision total shoulder arthroplasty, bone grafting severe glenoid defects without concomitant reinsertion of a glenoid prosthesis may be the only viable reconstructive option. However, the fate of these grafts is unknown. We questioned the durability and subsidence of the graft and the associated clinical outcomes in patients who have this procedure. We retrospectively reviewed 11 patients with severe glenoid deficiencies from aseptic loosening of a glenoid component who underwent conversion of a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 27 publications
(27 reference statements)
2
51
1
2
Order By: Relevance
“…Some authors prefer femoral allografts to reconstruct glenoid defects [1,6,10,17,26], but others suggest an autogenous iliac crest bone graft [5,14,27]. Neer and Morrison described the outcome for 20 shoulders that were treated for eccentric glenoid wear with a large segmental graft [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors prefer femoral allografts to reconstruct glenoid defects [1,6,10,17,26], but others suggest an autogenous iliac crest bone graft [5,14,27]. Neer and Morrison described the outcome for 20 shoulders that were treated for eccentric glenoid wear with a large segmental graft [15].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced erosion of the native glenoid can preclude future glenoid-revision arthroplasty [1,2]. As a salvage procedure, depending on the extent of the glenoid bone defect, Scalise et al suggest that bone grafting without concomitant glenoid component reimplantation may be a viable surgical option [10]. However, there is no data on whether prosthetic glenoid resurfacing results in greater pain relief than graft reconstruction of the glenoid alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glenoid can also be managed with a single-stage bone graft with or without reimplantation in anatomic TSA or RSA [19]. Scalise and Iannotti found that all 11 of their patients that underwent bone graft without reimplantation had significant subsidence and resorption though this did not correlate with clinical outcome scores [68]. One study showed that single-stage bone grafting with reimplantation of a glenoid component in three revision TSAs did not require further surgical intervention or show signs of loosening at a mean follow-up of 45 months [69].…”
Section: Glenoid Bone Lossmentioning
confidence: 99%
“…If there is inadequate bone, grafting can be performed with canellous graft in a two stage procedure as described by Cheung [71]. If there is a large cavitary defect with loss of the wall of the glenoid vault a structural allograft is likely indicated where bulk femoral head is contoured to the defect [72]. It is necessary to use these structural grafts when the wall is compromised as cancallous graft cannot be contained in these cases.…”
Section: Managing a Failed Glenoidmentioning
confidence: 99%